An investigation on the feasibility of applying MODIS snow cover products in cloudy weather by the employment of its integration with microwave images - majid vazifedoust; nima fayaz; shahab araghinejad (تحقیقات کاربردی علوم جغرافیایی)
Variation of snow cover area (SCA) in small to large scale catchment can be studied using MODIS snow products on daily to montly time step since the year 2000. However, one of the major problems in applying the MODIS snow products is cloud obscuration which limits the utilization of these products. In the current study, variation of SCA was investigated in Karoun basin, western part of Iran, using MODIS 8-day snow cover product (MOD10A2). More over in order to overcome the cloud barrier in application of snow cover products, a simultaneous employment of the images from both MODIS optical sensor and AMSR-E microwave sensor was recommended. Meeting our target, the combination of MODIS and AMSR-E daily images was exercised to accomplish snow cover area in daily interval and afterwards, a comparison was made between the result and those which had been obtained by the sole utilization of either of them while the weather had been either cloudy and not been overcast. Validation of snow cover gained by combined images was additionally compared with the discharge of one of the catchments existing in Karoun basin. The results demonstrate that regardless of the fact that microwave data, featuring a coarse spatial resolution, can penetrate the cloud cover, on average, AMSR-E images approximately show 16% more snow cover in comparison to MODIS images. The results also illustrate that the correlation existing between snow cover rate of AMSR-E and MODIS images during cloudless days, the difference of average snow cover area decreases from 16% to 5%. Moreover, the upshot of validation by the exercise of daily discharge data indicates that by possessing a correlation coefficient of 0.66, the correlation of snow cover and discharge in combined images features a higher accuracy in comparison to MODIS images with a correlation coefficient of 0.55.